Individual differences in stereotypy and neuron subtype translatome with TrkB deletion - Engeln, Michel; Song, Yang; Chandra, Ramesh; La, Ashley; Fox, Megan E.; Evans, Brianna; Turner, Makeda D.; Thomas, Shavin; Francis, T. Chase; Hertzano, Ronna; Lobo, Mary Kay (Molecular psychiatry, 2021)
Motor stereotypies occurring in early-onset neuropsychiatric diseases are associated with dysregulated basal ganglia direct-pathway activity. Disruptions in network connectivity through impaired neuronal structure have been implicated in both rodents and humans. However, the neurobiological mechanisms leading to direct-pathway neuron disconnectivity in stereotypy remain poorly understood. We have a mouse line with Tropomyosin receptor kinase B (TrkB) receptor deletion from D1-expressing cells (D1-Cre-flTrkB) in which a subset of animals shows repetitive rotations and head tics with juvenile onset. Here we demonstrate these behaviors may be associated with abnormal direct-pathway activity by reducing rotations using chemogenetic inhibition of dorsal striatum D1-medium spiny neurons (D1-MSNs) in both juvenile and young-adult mice. Taking advantage of phenotypical differences in animals with similar genotypes, we then interrogated the D1-MSN specific translatome associated with repetitive behavior by using RNA sequencing of ribosome-associated mRNA. Detailed translatome analysis followed by multiplexed gene expression assessment revealed profound alterations in neuronal projection and synaptic structure related genes in stereotypy mice. Examination of neuronal morphology demonstrated dendritic atrophy and dendritic spine loss in dorsal striatum D1-MSNs from mice with repetitive behavior. Together, our results uncover phenotype-specific molecular alterations in D1-MSNs that relate to morphological adaptations in mice displaying stereotypy behavior.